ANALISIS NILAI PERUSAHAAN PERSPEKTIF KEBIJAKAN UTANG DAN LABA: Studi Kasus pada PT Astra Internasional Periode 2012 - 2021 - Amthy Suraya (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to examine the effect of debt policy and profitability on the company value of PT Astra Internasional Tbk which is listed on the Indonesia Stock Exchange for the period 2012 - 2021. The population in this study is the entire financial statements of PT Astra Internasional Tbk which is listed on the Indonesia Stock Exchange 2012 - 2022. The research sample used in this study is in the form of balance sheet financial statements and financial statements of profit and loss of PT Astra Internasional Tbk which are listed on the Indonesia Stock Exchange for the period 2012 – 2021. The analytical method used is SPSS version 26.0 with the data analysis technique used is the classical assumption test, multicollinearity, heteroscedasticity, normality test, correlation and determination quotient test, simultaneous test and partial test. The results of the t-test study show a sig value of 0.699 > 0.05 and the tcount value is smaller than ttable or 0.403 <2.364 so it can be concluded that the Debt to Equity Ratio has no significant effect on Price to Book Value and the sig value is 0.086 > 0.05 and the tcount value is smaller from ttable or 1,993 <2,364 so it can be concluded that Return on Equity has no significant effect on Price to Book Value while the f-test results show Fcount 11,533 > Ftable 4.74 with a significance level of 0.006 which is smaller than the significant level of 0.05. so that the Debt to Equity Ratio (DER) and Return on Equity (ROE) together (simultaneously) has a significant effect on Price to Book Value (PBV).